DESIGN, SYNTHESIS AND STRUCTURAL ELUCIDATION OF ARYLOXYAMINOACETYLENIC DERIVATIVES AS ANTIDEPRESSANT ACTIVITY: Pharmaceutical Science-Medicinal Chemistry - A MUHI-ELDEEN, ZUHAIR; RANA G ABU-SAFIAH; ELHAM N AL-KAISSI; IBRAHIM S AL-ADHAM; NAJAH I AL-MUHTASEB (International Journal of Life Science and Pharma Research, 2019)
Depression is the most common illness that affects a large number of individuals in all countries. It is believed that decreased levels of neurotransmitters such as serotonin, norepinephrine and dopamine are the main cause of depression. Selective serotonin reuptake inhibitors (SSRIs) and norepinephrine reuptake inhibitors (SNRIs), their mechanism is to increase the amount of neurotransmitters in the CNS. Design, synthesis and molecular docking of novel compounds namely amino acetylenic derivatives of aryloxy as isostere for aryloxypropylamine. The reaction of 7-methoxy-2-naphthol with propargylbromide generated 7-methoxy-2-(prop-2-yn-1-yloxy) naphthalene (ZR-1). ZR-1 was subjected to Mannich reaction yielded the derivatives of aryloxybutynylamines (ZR-2 to ZR-7). The Mp, FTIR, 1H-NMR, C13-NMR, DSC, elemental analysis and HPLC were consistent with the assigned structures. The molecular docking results obtained for aminoacetylenic compounds showed that the new novel 7-methoxy-2- [4- (piperidine) but-2-yn-1-yl]oxy-naphthalene (ZR-4) provide effective π overlap with binding sites of SERT protein by ionic, hydrogen bonding and overlap of aryl and cyclic amine moieties with the amino acids of transporter protein, which produce the binding energy (-109,69 kcal/mol) for ZR-4 relative to paroxetine (-114.18 kcal/mol), that may lead to promising drug in the treatment of depression.